THE BOBY DIMENSIONS OF LOCAL CHICKENS AT THE PULLET PHASE AFTER L-THREONINE AND L-TRYPTOPHAN SUPPLEMENT IN FED - Charles Venirius Lisnahan; Oktovianus Rafael Nahak; Aurelia Abi (Journal of Tropical Animal Science and Technology, 2020)
ABSTRACT The purpose of this experiment was to know the body dimensions of Kampong chickens at the pullet phase after l-threonine and l-tryptophan supplement in the feed. This experiment was conducted in Kelurahan Sasi and the Laboratory of Agricultural Faculty, University of Timor, Kefamenanu from July 2019 to September 2019. The experiment used 96 fourteen-week kampong chickens, was designed with a Completely Randomized Design, consisting of 4 treatments and 4 replications. The dietary treatments were T0 (control feed), T1 (supplementation of 0.15% l-threonine and 0.06% l-tryptophan), T2 (supplementation of 0.37% l-threonine and 0.11% l-tryptophan), and T3 (supplementation of 0.50% l-threonine and 0.15% l-tryptophan). The variables measured were body weight, chest circle, sternum length, wing length, back length, femur, tibia, and shank circle. Data obtained was analyzed by analysis of variance and Duncan’s test. The result showed that the bodyweight of T0, T1, T2, and T3 were 1542.83±10.54, 1600.03±1.82, 1638.49±14.97, and 1716.85±23.84 g/bird, respectively. The chest circle, wing length, back length, sternum length, femur, tibia, circle and length of shank were 26.20±1.87, 26.38±0.47, 28.63±2.21, and 29.83±1.83 cm/bird; 17.78±1.00, 17.98±0.36, 18.75±0.95, and 19.85±1.63 cm/bird; 15.75±0.64, 16.50±1.08, 18.50±0.57, and 18.38±0.85 cm/bird; 12.93±1.77, 13.75±1.19, 13.88±0.85, and 14.73±0.48 cm/bird; 10.50±0.70, 10.93±1.20, 10.95±0.10, and 11.73±0.73 g/bird; 10.70±0.50, 11.10±0.89, 12.23±0.58, and 12.15±0.57 cm/bird; 4.23±0.05, 4.20±0.21, 4.23±0.22, and 4.40±0.20 cm/bird; and 8.90±0.11; 8.88±0.47; 9.13±0.62, and 10.38±0.62 cm/bird, respectively. Statistical analysis showed that levels of l-threonine and l-tryptophan significantly affected body weight, chest circle, sternum length, wing length, and back length (P<0,05). It was concluded that supplementation with 0.50% l-threonine and 0.15% l-tryptophan to the diet increases the body dimensions kampong chickens at the pullet phase.